Spirituality on the Blog - Interpretation of the Narrative of a SMA Patient - Katarzyna Ciszewska (Jesuit University Ignatianum in Krakow, 2022)
RESEARCH OBJECTIVE: The main goal of this article is to try to recognize the importance of spirituality in the process of dealing with SMA described on the patient's blog. PROBLEM AND RESEARCH METHODS: We searched for answers to questions about the importance of spirituality in the context of struggling with the disease, religious coping strategies, and the way of growing in faith shown on the blog. A research approach was used, embedded in an interpretative paradigm, aimed at understanding and discovering the meanings given by the author of the narrative.  THE PROCESS OF ARGUMENTATION: The introduction contains a description of the SMA, characterizes the blog as a research source and outlines the subject of the text. In the next section, the categories of spirituality and religious strategies for coping with disease are characterized, and research on the relationship between spirituality and health is reviewed. The presentation describes the methods used and the results of own research. In conclusion, an attempt was made to define the meaning of spirituality in the patient's life in the context of his life with the disease. The implications for pedagogical practice include reflections on the role of accompaniment in illness in the context of spiritual growth.  RESEARCH RESULTS: Spirituality is an important part of the author's life - he searched for answers regarding the meaning of suffering. He most often used a religious coping strategy through positive reevaluation (Harrison et al., 2001). The main motive for writing about transcendence seems to be the need to give a testimony. The blog is an illustration of the process of growing in faith. CONCLUSIONS, INNOVATIONS, RECOMMENDATIONS: The blog is a source of knowledge about patients' experiences, helpful for specialists. Accompanying the sick person and listening to their history can be of educational value for both parties.